An experimental assiduity on the dominance of process parameters on mechanical properties for making a fire retardant bamboo fiber composite with the help of Taguchi experimental design. (2018) - Banik, Nabanita; Dey, Vidyut; Sastry, G.R.K.
Abstract: Astringent Government regulations, A Hard Nut to Crack disposal, augmentative oil prices, dwindling fossil fuels & predominant environmental cognition concerned to the use of petroleum based products has forced the manufacturers to seek for eco-friendly & sustainable materials, that trace the problems associated with synthetic composites with an endurable solution to replace themselves with natural fibers. From the past decades it has been shown that apart from the prosperous civilian living standard & sustainability of environment, fiber reinforced composites using range belongs from aerospace applications to military & automobile industries for continuously advancing in order to meet their new challenges due to its flexibility in intended design i.e., capability of tailoring two or more materials as per required specification. Besides the biodegradability & eco-friendly behaviour another most important thing is fire retardant & termite resistant properties. Fire always has been an intensive threat to the well-being entity of the civilization due to the monetary damages, substantial injuries & huge losses of heart's-blood. In the mob of innovating environmental durable composite material, combustible peculiarity may have avowed titular consideration. In another point of view the major problem associated with the natural fiber reinforced composites is the fall of physical strength due to the attack of borer beetles & termite. Pertaining these problems one enthusiasm has taken in this ploy to develop more deft & limber composite by optimizing the process parameters with Taguchi L16 orthogonal array design experiment. By applying the analysis of the signal-to-noise ratio (S/N ratio) & analysis of variance (ANOVA) the optimum combination of process parameters & the importance of the levels have been ascertained in some respects. Dispense of regression analysis were mathematically modeled the metamorphism of mechanical properties with process parameters. Eventually, the presented models are also substantiated by a set of confirmation test.